Features of birth rate in the Republic of Tuva (1991–2021) - Rostovskaya, Tamara K.; Zolotareva, Olga A.; Davletshina, Leysan A. (The New Research of Tuva, 2023)
The article presents a retrospective dynamics of the total birth rate for 30 years and an analysis of changes in the rating of the Republic of Tuva on this indicator. The study allows us to formulate hypotheses of the impact of the demographic policy on the increase in natality in the region and, in particular, to consider the effect of the introduction of regional maternity capital in Tuva. The research is based on methods of generalization and synthesis, descriptive statistics techniques, in particular, for pursuing a comparative analysis of changes in the position or place of the Republic of Tuva among all Russian regions by the total fertility rate (calculation of median values, determination of quartiles in distributions, construction of a scattering diagram).We specify an assessment of changes in the main indicators of the birth rate of the population in the Republic of Tuva and identify two periods of demographic development. The first period was between 1991 and 2006. Its distinctive characteristic is that the average annual total birth rate was 2.23 births per woman of reproductive age. In the second period (2007–2021), there was a higher average annual value of the total fertility rate. It was 3.10 births per woman of reproductive age.Trends in age-related birth rate have shown that there is the problem of aging of fertility. This requires special attention and measures to curb the strengthening of this trend when there is a young population structure in the region. The consideration of the age-related characteristics of birth rate has revealed an increase in the modal value of age-related fertility rates amid an increase in the age of marriage among both men and women.
Keywords: natural population growth; birth rate dynamics; total fertility rate; age-related fertility rates; marriage rates; age and gender structure of marriage